AKTIVITAS INHIBISI α-GLUKOSIDASE DARI EKSTRAK AIR DAN ETANOL DAUN SIMPUR AIR (Dillenia suffruticosa (Griff.) Martelli) - Sitaresmi Yuningtyas; Anna P. Roswiem; Erfina (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Diabetes mellitus is a disorder of carbohydrate metabolism which characterized by hyperglycemia conditions. One of the mechanism from oral hypoglycemic drug is inhibition of α-glucosidase activity. Dillenia suffruticosa (Griff.) Martelli, known as